TRAINING ON TUNA FISH PROCESSING "MINA SARI" SME’S WITH SPINNER IMPLEMENTATION IN MALANG REGENCY. - zainal abidin (Journal of Innovation and Applied Technology, 2017)
Fish abon processing is one of fish products diversification. Tuna fish abon contains protein, fat, water and ash, respectively for 27.94%; 13.03%; 3.52%; and 3.53%. Production management of tuna fish abon "Minasari" was not effective yet. Marketing scope also was not wide yet due to its expired date only 6 months. Science and technology programs for the public (IbM) in 2014 introduced a spinner technology aimed to develop micro-enterprises tuna fish abon. The method used were focus group discussions, training, counseling, technology demo, as well as coaching and mentoring business management. Outcomes achieved are tuna fish abon product have nine months expired date and wider marketing; processing methods of tuna fish abon more efficient using spinner. Coaching by observing practices of planning and implementation of raw materials stocking management, efficient processing methods, the use of spinner, financial analysis, planning and implementation of marketing mix. Entrepreneur of tuna fish abon Minasari should expand marketing efforts by consignment system with food shop in some Tourism objects close to Sendangbiru, Malang souvenirs shop and frozen store. Beside that, it needs promotion by online and practice a simple business finance to be easier evaluating profitability performance.